CONTRACEPTIVE CHOICE AMONGST WOMEN IN WARRI, NIGERIA: Life Science-Gynaecology - DR AWUSI; VINCENT; OGHENEKOBARO (International Journal of Life Science and Pharma Research, 2012)
Background: Contraceptive choice could assist family planning clinics in determining the type of contraceptive devices to be supplied as well as in devising a strategy for improving contraceptive acceptance. Aim: To determine the choice of contraceptive usage and the factors predictive of such choices in Warri, southern Nigeria. Design: A cross-sectional study. Setting: Delta State University Teaching Hospital, Warri (temporary site), Nigeria. Subjects: Clients attending the family planning clinic. Main outcome measures: contraceptive choice, reason for choice, awareness and source of awareness about contraceptives. Result: Five hundred respondents were interviewed. Ninety-six percent knew at least one method of contraception. Their ages ranged between 17 and 50 years. Majority were in the age group 31–35 years(44.2%), housewives(38.4%), attained secondary school education or more (76.4%), were married (87.4%), in monogamous marriages(78.6%) and grand multiparous (47.8%). The commonest contraceptive choice was the injectables(51.0%); and nurses/midwives formed the commonest source of knowledge about contraception and referral. Conclusion: The injectable was the most preferred contraceptive method by the women in Warri, Nigeria. The HIV/AIDS pandemic may change this trend.